Roque Callage e os esquecidos d'A Cidade : a exclusão social em Porto Alegre através do olhar de um cronista (1925-1930) - Perin, Henrique (2017)
The present dissertation aims to understand how the journalist, writer and chronicler Roque Callage perceived the process of social exclusion in the city of Porto Alegre between the years of 1925 and 1930 and related to the column A Cidade, in the Diário de Notícias’s newspaper. The universe of excluded and marginalized whose the chronicler wrote in his column - workers, employees, beggars, flagellates, poor children, suicides, lepers, immigrants, just to name a few - earns their place in Porto Alegre society through the look of Callage. The formation of the press in Rio Grande do Sul, as well the intellectuality era of the first decades of the twentieth century and a constitution of the Diário de Notícias in Porto Alegre, are essential to understand the environment that the chronicler was inserted. The relation of alterity between the rich and the poor population, having as stage the city streets; the bad working conditions of the employees, the problems of food, housing and sanitation for a working population, are reported by the columnist and analyzed through concepts of working class experience. The flagellates, poor children, beggars and morphetics, in addition to services provided by charities institutes, are rescued and analyzed according to exclusionary concepts of sociologists and social history theorists. This formation of experiences among the marginalized groups, a perception of the chronicler of this part of the population and its later publication in the column of A Cidade, help to form the picture of "forgotten" through which Callage presents a distinct presentation of the elegant meetings, footings and vernissages of the Society of Porto Alegre.